مظاهر الصراع في ملحمة جلجامش واثرها في فهم مجتمع العراق القديم - فهد حسين ا.م.د محمد (Journal of College of Education, 2021)
The Epic of Gilgamesh of the most important literary relics witnessed by human civilization throughout its ancient history , this saga of a whale on many topics of importance urgent major humanitarian questions such as life and death and immortality, urbanization and urbanization, love and hate and upper values of good and evil and the unseen , and other concepts ever-important link in all human society. Perhaps one of the things that was full of them this epic much is conflict, and the conflict was in the Epic of Gilgamesh diverse and entangled it has included almost every kind of conflict between the assets as a whale on the conflict with humans, animals and inanimate objects and creatures unseen and even the gods, all of which lived moments of bitter conflict and parking annexed this epic. The conflict in general is the subject of a deliberate in the ancient civilization of Iraq, but his studies independently in the Epic of Gilgamesh, as well as a statement projections and what we can find to link between him and the community formats in the ancient Iraq, said all of this leads us to say that this topic could be a new in their respective fields. Follow the search analytical method and Correlative , The curriculum analytical analyze conflict situations and backgrounds of staff, and what are its causes, either Correlative approach aims to link these conflict situations and what can be deduced from our influence on the behavior and activities of the community in the ancient Iraq.